1971
DOI: 10.1111/j.1365-2621.1971.tb01610.x
|View full text |Cite
|
Sign up to set email alerts
|

The control and evaluation of spoilage *

Abstract: Methods currently used in the control and evaluation of spoilage of meat are reviewed and their value discussed. In many instances scientific explanations of the effectiveness of the control methods are lacking, e.g. the mechanism of action of carbon dioxide or sodium nitrite in controlling microbial growth. A lack of knowledge regarding the chemical and biochemical processes involved in spoilage hinders the development of completely satisfactory methods of spoilage evaluation. Research directed towards rectif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Dainty (1971) concluded that a combination of three approaches could be utilized to control storage: preventing initial bacterial contamination, inactivating bacteria present or utilizing storage conditions to prevent or slow bacterial growth. For opportunistic bacterial infections resulting from a pathological consequence of stress the most important factor is good handling and storage.…”
Section: Discussionmentioning
confidence: 99%
“…Dainty (1971) concluded that a combination of three approaches could be utilized to control storage: preventing initial bacterial contamination, inactivating bacteria present or utilizing storage conditions to prevent or slow bacterial growth. For opportunistic bacterial infections resulting from a pathological consequence of stress the most important factor is good handling and storage.…”
Section: Discussionmentioning
confidence: 99%
“…If the animal has been excited or starved prior to slaughter and depletes the glycogen reserve in the muscle, the ultimate pH reached will be higher than pH 5.5. The closer to neutrality the ultimate pH is, the faster the growth of microorganisms in or on the meat (Dainty, 1971;Rey et al, 1976;Patterson and Gibbs, 1977).…”
Section: Meat Trimmings and Fat Can Bementioning
confidence: 99%
“…These results support her findings. Jaye Dainty (1971) reported that the breakdown of fats by bacteria is relatively what less offensive than the odor from the low barrier chops. Odor throughout the study was difficult to charac terize both quantitatively and qualitatively.…”
Section: Tenderness For Both Loin Storage Periods Was Approximatelymentioning
confidence: 99%
“…These results support her findings. Jaye Dainty (1971) reported that the breakdown of fats by bacteria is relatively…”
Section: Effect Of Packaging Film Onmentioning
confidence: 99%
“…If the animal has been excited or starved prior to slaughter and depletes the glycogen reserve in the muscle, the ultimate pH reached will be higher than pH 5.5. The closer to neutrality the ultimate pH is, the faster the growth of microorganisms in or on the meat (Dainty, 1971;Rey et al, 1976;Patterson and Gibbs, 1977). (Lechowich, 1971).…”
mentioning
confidence: 99%